Who killed Stalin - Robinson, Tim ([United Kingdom] : BBC, 2005)
A re-appraisal of the death of 20th century dictator, Stalin. Was the official account of Stalin's death a cover-up for what really happened? Secret KGB files are examined for the first time to discover the truth.
Title from title screen
Narrator, Michael Praed.
dvd format
Keywords: Stalin, Joseph, -- 1879-1953 -- Death and burial; Soviet Union -- Politics and government -- 1936-1953.